HUBUNGAN ANTARA PENYAKIT ARTERI PERIFER DENGAN FAKTOR RISIKO KARDIOVASKULAR PADA PASIEN DM TIPE 2 - Simatupang, Maria; Pandelaki, Karel; Panda, Agens L. (Universitas Sam Ratulangi, 2013)
Abtract: Peripheral arterial disease (PAD) is one of the complications that occurs in patients with type 2 diabetes mellitus due to the process of atherosclerosis. Age, hypertension, obesity, LDL cholesterol, and smoking are the cardiovascular risk factors that can be found in diabetes patients. Ankle brachial index (ABI) is a simple way to confirm the diagnosis of PAD. This study used a cross sectional design. The subjects numbered 100 patients with type 2 diabetes mellitus who were examined in the Metabolic Endocrine Clinic of Prof. Dr. R.D Kandou Hospital. Data of variables were based on the patients’ medical records, interviews about smoking, and blood pressures measured on ​​legs and arms in a supine position. A Chi-square test showed that there was a correlation between blood pressure and ABI values ​​(P = 0.049). Moreover, there was no correlation between risk factors of age (P = 0.144), obesity (P = 0.488), LDL cholesterol (P = 0.197), and smoking (P = 0.512) with ABI values. Multivariate analysis showed that there was a significant correlation between blood pressures and ABI values ​​(P = 0.037). Conclusion: From all the examined cardiovascular risks, the most correlated with the incidence of PAD in patients with type 2 diabetes mellitus was blood pressure. Keywords: cardiovascular risk factors, PAD, type 2 diabetes mellitus Abstrak: Penyakit Arteri Perifer (PAP) merupakan salah satu komplikasi yang terjadi pada pasien diabetes melitus tipe 2 (DMT2) akibat proses aterosklerosis. Usia, hipertensi, obesitas, kadar kolesterol LDL dan merokok merupakan faktor risiko kardiovaskular yang dapat ditemukan pada pasien diabetes. Ankle Brachial Index (ABI) merupakan cara sederhana untuk mendiagnosis PAP. Penelitian ini menggunakan desain cross sectional. Subjek dalam penelitian ini berjumlah 100 pasien DMT2 yang melakukan pemeriksaan di Poliklinik Endokrin Metabolik RSUP Prof.Dr.R.D. Kandou Manado. Pengukuran variabel berdasarkan pada catatan rekam medik pasien, anamnesis riwayat merokok, dan pengukuran nilai tekanan darah kaki maupun tangan dalam posisi berbaring. Uji chi-square menunjukkan bahwa terdapat hubungan bermakna antara tekanan darah dan nilai ABI (P = 0,049), sedangkan faktor risiko usia (P = 0,144), obesitas (P = 0,488), kolesterol LDL (P = 0,197) dan riwayat merokok (P = 0,512) tidak didapati adanya hubungan. Analisis multivariat, menunjukkan bahwa terdapat hubungan yang sangat bermakna antara tekanan darah dengan nilai ABI (P = 0,037). Simpulan: Dari semua faktor risiko kardiovaskular yang di teliti, tekanan darah yang paling berhubungan dengan kejadian PAP pada pasien DMT2. Kata kunci: DMT2, faktor risiko kardiovaskular, PAP